Performance and participation in evaluation of development assistance in Asia - Snyder, Monteze M. (1995)
The performance questions and measures used in assessing (donor) USAID Development Assistance is as important as the aid itself. For the evoluation to be most useful, techniques count as much as processes. Local consultants with technical knowledge and indigenous experience can contribute much to the success of evaluation
Keywords: International economic relations; Foreign aid